Effect of Kembang Bulan Leaf (Tithonia diversifolia) Ethanolic Extract to SGOT and SGPT Levels in Diabetic Rats (Rattus norvegicus) - Achmad Firdaus Pamudya Wardhana; Arifa Mustika; Citrawati Dyah Kenconowungu (Indonesian Andrology and Biomedical Journal, 2021)
Introduction: Kembang Bulan (Tithonia diversifolia) is one of Indonesian traditional medicine that contains saponins, flavonoids, and, tannins and is predicted has a lowering effect on blood-glucose. Diabetes mellitus (DM) is a disease caused by insufficient insulin secretory by the pancreas or ineffective usage of insulin that produced by the body thus cause a hyperglycemia condition. Hyperglycemia can cause an increase in Reactive Oxygen Species which can cause free radicals. Free radicals can cause damage to liver cells. Method: This was an experiment with posttest control group design. Samples were 40 rats, divided into five different groups (P1, P2, P3, P4 and P5). Each group were induced by multiple low doses STZ. P1 (give the extract of Tithonia diversifolia at a dose 50 mg/100 gr BB), P2 (give the extract of Tithonia diversifolia at a dose 150 mg/100 gr BB), and P3 (give the extract of Tithonia diversifolia at a dose 450 mg/100 gr BB), P4 was treated with metformin, P5 was not treated. After STZ induction and give the extract to diabetic rat model, the resulting liver cell damage will be measured using the SGOT and SGPT measurement methods. Result: On the average results of SGOT levels in the five treatments, using the ANOVA test p value was 0.877 (p> 0.05) which means there were no significant differences. Furthermore, on the average results of SGPT levels in all five treatments, using the ANOVA test p value was 0.822 (p> 0.05) which means there were no significant differences. But from all results obtained P4 (given metformin) with the results closest to normal levels (SGOT: 197.5 ± 37.25; SGPT: 90.33 ± 29.36). From the treatment given Tithonia diversifolia extract obtained P1 (with a dose of 50 mg / 200gr BB) with the results closest to normal levels compared to P2 and P3. Conclusion: The Extract of kembang Bulan Leaf (Tithonia diversifolia) obtained less significant results compared to the untreated group. However, there is no significant difference. And giving ethanol extract of the leaves of kembang Bulan (Tithonia diversifolia) at a dose of 50 mg / 100gr BB is the most effective way to reduce levels of SGOT and SGPT.